Postpartum quality of life after normal vaginal delivery and caesarean section - Amatya, Yogendra; Acharya, Samita (Journal of Patan Academy of Health Sciences, 2015)
Introductions: Caesarean section is rising. The best method of delivery, vaginal or caesarean, for postpartum quality of life in women is a matter of controversy both from professionals’ perspectives and from women’s experience of childbirth. This study analyses quality of life after these two methods of deliveries. Methods: This was a cross-sectional comparative study in postnatal care outpatient department at Patan Hospital. Primipara women with normal delivery and elective caesarean section done in Patan Hospital were enrolled to analyse postpartum quality of life. The SF-12 questionnaire tool at 6 weeks post delivery was used to compare age, ethnicity, education, family type and employment. Data was analysed using ANOVA test for descriptive parameters. Results: There were 468 primipara, age 30-45 years, 94% in 15-30 years77.8% educated, 74.4% in joint family,73.5% housewife. Normal vaginal delivery was 360 (72.6%) and 128 (27.4%) elective caesarean. Vaginal delivery group had average SF score of Physical Health Composite Score of 68.7, Mental Health CompositeScore69.5 and total SF score 67.7. While in caesarean group, it was 64.8,64.1 and 63.4. Conclusions: Normal vaginal delivery had better quality of life resulting in both superior physical as well as mental health. Journal of Patan Academy of Health Sciences, Vol. 2, No. 2, 2015. page:13-18